ANALYSIS OF THE IMPLEMENTATION OF EFFORTS TO INCREASE THE VALUE OF LOCAL WISDOM FOR THE MILLENNIAL GENERATION IN THE DIGITAL AGE - Widia Firta; Rama Putra, Dike; Pratama, Rahmatullah (Adisam Publisher, 2024)
Entering the millennial era which is called the technological era where technology is developing rapidly in various regions and this technology is developing rapidly in various millennial generations. With today's technological sophistication, the ability to increase local cultural wisdom is certainly very influential and not all millennial generations can adapt to this. The role of the millennial generation is very important in maintaining local wisdom culture today. This role will affect the surrounding environment. In responding to technological developments, it is very difficult for the millennial generation to carry out the role we take in local wisdom and sometimes there are still those who cannot maximize this situation. One of their roles is that as the millennial generation